The Exodus of Talent: Analyzing Brain Drain in Nepal - Poudel, Bibas; Shrestha, Saksham (Far Western Review, 2024)
Brain drain, the emigration of skilled professionals from developing to developed nations, has emerged as a critical challenge for Nepal. Nepal has been experiencing a severe exodus of young and qualified professionals in the last decades leading to labor shortages and diminished innovation capacity. Addressing the brain drain issue is required for the long-term development of the nation. The study aims to review the existing literature on trends, causes, and impacts of brain drain in Nepal seeking possible solutions to control this exodus. Various secondary data sources were used to review the existing data and literature on brain drain in Nepal and descriptive approaches were utilized to analyze them. Various pull and push factors have contributed to brain drain in Nepal. The study finds that inadequate job opportunities, political instability, low wages, and limited research and development (R&D) investments are key push factors driving skilled migration. Simultaneously, developed nations attract Nepalese talent through better employment prospects, higher salaries, and superior education systems. While remittances from migrant workers have significantly contributed to Nepal’s economy, the outflow of human capital has resulted in labor shortages in crucial sectors such as healthcare, education, and technology. Furthermore, the reliance on remittances risks long-term economic stagnation and reduced innovation capacity. To mitigate brain drain, Nepal must implement policies that foster job creation, invest in higher education and research, and establish returnee-friendly programs. Drawing from global examples, the study recommends strategies to retain skilled professionals and encourage their return, ensuring sustainable economic and social development.